Examination of The Legal Regime for Combatting Trafficking in Persons in Nigeria - Kingsley Osinachi N. Onu (Institute Of computer Science (IOCS), 2022)
Human trafficking is one of the biggest challenges of the 21st Century. The Sub Saharan Africa seems to be the center point of this global epidemic. Nigeria is an origin, transit and destination point for global trafficking in persons. This paper uses a doctrinal research approach to examine the legal regime for combatting trafficking in persons in Nigeria and argues that Nigeria must be more proactive in its fight against human trafficking. This paper finds that poverty, weak legal system, armed conflicts, climate change, family imbalance and greed among other factors, contribute to trafficking in persons. This paper finds that there exist a plethora of legislations on human trafficking in Nigeria, such as the Constitution of the Federal Republic of Nigeria 1999, as amended in 2018; Trafficking in Persons (Prohibition) Law Enforcement and Administration Act, 2015; the Immigration Act 2015; the Criminal and Penal Code Acts; the Child’s Right Act and the African Charter. This paper finds that these extant legal frameworks in Nigeria are frost with several lacunas that will hamper and ultimately defeat the fight against human trafficking. The paper therefore makes suggestions on how to remedy the observed lacuna. The paper concludes by stating that the fight against human trafficking must be a collective effort by all. Human rights are not safe anywhere until all persons have enough of the same everywhere.